Efektivitas Media Pembelajaran Digital Quizizz sebagai Media Evaluasi Peserta Didik Bahasa Indonesia Kelas IX Materi Cerita Pendek di SMP Negeri 1 Singosari - Kusuma, Bima Ertha; Bafana, Abdul Faiq; Abadi, Machrus (Multiverse: Open Multidisciplinary Journal, 2023)
In the 21st century, digital technology plays an increasingly crucial role in student motivation. The utilization of digital technology not only facilitates the rapid acquisition of information but also enhances life skills, thereby simplifying the process for educators to create learning materials. This research adopts a whole group pre-experimental design model, with the student population and sample drawn from classes IX-A and IX-D at SMPN 1 Singosari. Class IX-A serves as the experimental group, while class IX-D functions as the control group. Data collection employs triangulation techniques, encompassing observation, interviews, and documentation, complemented by an instrument test utilizing short story material. Subsequent analysis of the test results employs descriptive quantitative methods, involving a comparative assessment to draw conclusions regarding the effectiveness of Quizizz media as an evaluation tool for short story text material.